2021
DOI: 10.1007/s10353-021-00730-y
|View full text |Cite
|
Sign up to set email alerts
|

Wound myiasis in Western Europe: prevalence and risk factors in a changing climate scenario

Abstract: Summary Background Myiasis is an infestation of neglected open wounds by fly larvae. Global warming, related climate changes, and increased traveling in tropical countries may contribute to the worldwide diffusion of new fly species. Common risk factors for myiasis are advanced age, poor hygiene, malnourishment, social isolation, diabetes, cancer, and peripheral artery disease. The aim of this study was to review the characteristics of cases of myiasis reported in Europe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Since L. sericata has a worldwide distribution, myiasis in birds by this species has been reported to date in Austria, Finland, Hungary, Iran, Iraq, Israel, Peru and Turkey ( Table 1 ). In Italy, L. sericata has been reported as an agent of myiasis since the early 1900s in humans [ 48 , 49 , 50 , 51 , 52 , 53 ] and in cats [ 54 , 55 , 56 ], dogs [ 54 , 57 , 58 ], sheep [ 54 ] and a rabbit [ 59 ]. Among other myiasigenous species reported in animals in Italy, there are Oestrus ovis (Linnaeus) (Diptera: Oestridae) [ 60 ], W. magnifica [ 61 ], Sarcophaga argyrostoma (Robineau-Desvoidy) [ 56 ], Sarcophaga portschinskyi (Rohdendorf) [ 57 ], Sarcophaga tibialis Macquart (Diptera: Sarcophagidae) [ 55 ], C. vicina [ 56 , 58 , 62 ], Lucilia ampullacea Villeneuve (Diptera: Calliphoridae) [ 54 ], L. caesar [ 63 ], L. illustris [ 54 ] and Muscina stabulans (Fallén) (Diptera: Muscidae) [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since L. sericata has a worldwide distribution, myiasis in birds by this species has been reported to date in Austria, Finland, Hungary, Iran, Iraq, Israel, Peru and Turkey ( Table 1 ). In Italy, L. sericata has been reported as an agent of myiasis since the early 1900s in humans [ 48 , 49 , 50 , 51 , 52 , 53 ] and in cats [ 54 , 55 , 56 ], dogs [ 54 , 57 , 58 ], sheep [ 54 ] and a rabbit [ 59 ]. Among other myiasigenous species reported in animals in Italy, there are Oestrus ovis (Linnaeus) (Diptera: Oestridae) [ 60 ], W. magnifica [ 61 ], Sarcophaga argyrostoma (Robineau-Desvoidy) [ 56 ], Sarcophaga portschinskyi (Rohdendorf) [ 57 ], Sarcophaga tibialis Macquart (Diptera: Sarcophagidae) [ 55 ], C. vicina [ 56 , 58 , 62 ], Lucilia ampullacea Villeneuve (Diptera: Calliphoridae) [ 54 ], L. caesar [ 63 ], L. illustris [ 54 ] and Muscina stabulans (Fallén) (Diptera: Muscidae) [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides the rural hilly area (around 700 a. s. l.) where the present case occurred in Southern Italy, this species has been reported as an agent of myiasis in animals in lowland rural areas of Northern Italy [ 55 , 56 , 58 ]. Based on the literature data, apparently, this species is an agent of myiasis affecting animals and humans in most of the Italian territory [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. The most common type of myiasis caused by L. sericata in birds worldwide is cutaneous myiasis, with wounds as a predisposing condition, especially caused by bone fractures due to severe traumas ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thorough irrigation with normal saline promotes the clearance of any remnant turpentine oil. Many agents can be used for the removal of maggots, such as oil of turpentine, mineral oil, ether, chloroform, ethyl chloride, mercuric chloride, creosote, saline, phenol, calomel, olive oil, iodoform applied locally followed by manual removal, or surgical debridement [ 11 ]. In severe cases, even a triple-drug regimen of tablet ivermectin 12 mg per day for three days, tablet albendazole 400 mg twice per day for three days, and tablet clindamycin 300 mg three times per day for five days could be considered [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, even after the complete mechanical removal of the maggots during the patient's first visit, some larvae had developed by the time of the second visit. Hence, we developed a comprehensive treatment protocol [5][6][7][8][9][10][11][12] promoting the stepwise removal of maggots, which also includes a follow-up after one week.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling scientific literature have revealed that a significant rise in temperature or humidity will increase the growth and redistribution of most myiasis-causing flies, subsequently increasing myiasis infestation in such regions [ 11 , 14 ]. Some factors that influence this dermatosis in SSA are high humidity and temperature (especially during the rainy season) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%